Pengaruh Green Relational Capital, Green Structural Capital, And Green Human Capital Terhadap Kinerja Perusahaan - Patuan Belt Sazar Sihombing; Etty Murwaningsari (Politeknik Ganesha Medan, 2023)
The purpose of this research is to evaluate how green relational, structural, and human capital impact corporate performance, with leverage functioning as a moderator. The annual and sustainability reports from non-financial enterprises listed on the IDX in 2020–2021 are among the unbalanced data utilized in this analysis. The website of the Indonesian Stock Exchange (IDX) supplied the information for this research. Predictions suggest that 131 non-financial enterprises will list in 2020 and 238 in 2021. The sample, which was constructed from discoveries that fit the criteria, contained 334 companies. According to the study's results, green structural capital and green human capital (GHC) are harmful to a company's growth. This is because there aren't enough resources available to invest in technology or human resources that can foresee environmental repercussions. The success of an organization is also tied to its green relational capital. In order to expand their capacity, skill, and knowledge and to generate new goods more fast and more cheaply, the majority of manufacturing enterprises are creating strong ties with their suppliers. These relationships are advantageous to corporate sustainability. The data also show that leverage weakens the impact of green relational capital (GRC) while strengthening the relationship between green human capital (GHC), green structural capital (GSC), and company success.